Manejo comportamental em Odontopediatria – uma revisão de literatura - Mangoni, Nátalli (2021)
Fear and anxiety can be considered two enemies of dentists, especially pediatric dentists, as they interfere with patients' behavior and often prevent treatment. The present work aimed to seek, through the literature, to know the behavioral management techniques that can minimize fear and anxiety during dental care in children's patients. Literary searches on this subject were carried out in Pubmed, Scielo, Google Scholar databases. The researched literature registers forms of behavioral control, as well as means for the use of tests that identify fear, anxiety and even the professional situation. It is concluded that the best technique to be used is the one that best adapts to the situation being experienced in the office, as long as it does not violate the Child and Adolescent Statute and its legal and ethical aspects.